(untitled) (Italian Journal of Public Health, 2012)
For the last seven years, the European Academies Science Advisory Council (EASAC) has conducted a series of projects defining and clarifying priorities for European policy in infectious disease. Both human and animal populations are increasingly threatened by emerging and re-emerging infections, including zoonoses, partly attributable to the impact of environmental change on the distributions of pathogens, hosts and vectors. Among the key challenges to be faced are the impact of climate change, the increase of antibiotic resistance and the need to develop novel global surveillance and early warning systems worldwide. Multidisciplinary approaches are required to build the new interfaces between human and animal medicine (One Health), with new connections between epidemiological and environmental data for surveillance, communication and risk assessment. This multidisciplinarity involves integration between microbiology, immunology, genetics and genomics, entomology, ecology and the social sciences, among other disciplines. Improved understanding of patterns of both human and animal disease also requires commitment to standardisation of surveillance methodologies and better analysis, co-ordination and use of the data collected. There must be sustained support for fundamental research, for example to explore how pathogens cross the species barrier, encouragement for industry innovation in developing diagnostics, therapeutics and vaccines, and the increased use of scientific evidence to inform coherent strategic development across different policy-making functions and to support international leadership. Our paper is intended as an introduction to some of the issues for building collaboration between human and animal medicine, to be discussed in greater detail in the other contributions to this Issue....